Association of transcatheter edge-to-edge repair with improved survival in older patients with severe, symptomatic degenerative mitral regurgitation. (28th January 2022) - Benfari, Giovanni; Sorajja, Paul; Pedrazzini, Giovanni; Taramasso, Maurizio; Gavazzoni, Mara; Biasco, Luigi; Essayagh, Benjamin; Grigioni, Francesco; Bae, Richard; Tribouilloy, Christophe; Vanoverschelde, Jean-Louis; Michelena, Hector; et al.
Abstract: Background: Randomized clinical trials demonstrated transcatheter edge-to-edge repair (TEER) efficacy in improving outcome vs. medical management for functional mitral regurgitation, but limited randomized data are available for the treatment of degenerative mitral regurgitation (DMR). We aimed to compare the outcome of older patients treated with TEER vs. unoperated DMR. Methods and results: Registries including consecutive patients ≥65 years with symptomatic severe DMR treated with TEER (MitraSwiss and Minneapolis Heart Institute registries) or unoperated (MIDA registry) were analysed. Survival was compared overall and after matching for age, sex, EuroSCORE II, and ejection fraction. The study included 1187 patients (872 treated with TEER and 315 unoperated). During 24 ± 17 months of follow-up, 430 patients died, 18 ± 1% at 1 year and 50 ± 2% at 4 years. Patients undergoing TEER had similar age (82 ± 6 vs. 82 ± 7 years) and sex to unoperated patients, but higher surgical risk/comorbidity (EuroSCORE II 3.98 ± 4.28% vs. 2.77 ± 2.46%), more symptoms, and atrial fibrillation ( P < 0.0001). Transcatheter edge-to-edge repair was associated with lower mortality accounting for age, sex, EuroSCORE II, New York Heart Association class, atrial fibrillation, and ejection fraction [hazard ratio (HR): 0.47, 95% confidence interval (CI): 0.37–0.58; P < 0.0001]. After propensity matching (247 pairs of patients), TEER consistently showed better survival compared with unoperated patients (49 ± 6% vs. 37 ± 3% at 4 years, P < 0.0001) even in comprehensive multivariable analysis (HR: 0.60, 95% CI: 0.40–0.91; P = 0.03). Procedural failure was infrequent but post-procedural mitral regurgitation, remaining moderate-to-severe in 66 (7.6%) patients, was associated with excess mortality vs. trivial residual regurgitation (30 ± 6% vs. 11 ± 1% at 1 year, P < 0.0001). Conclusion: Amongst older patients with severe symptomatic DMR at high surgical risk, mitral TEER was associated with higher survival vs. unoperated patients. Successful control of mitral regurgitation was key to survival improvement with mitral TEER, which should be actively considered in patients deemed inoperable. Structured Graphical Abstract: Structured Graphical Abstract Comparison of patients with degenerative mitral regurgitation treated with transcatheter edge-to-edge mitral valve repair vs. unoperated.